Análise parasitológica de solo do entorno de instituições de saúde de Mossoró, Rio Grande do Norte - Carvalho, Amanda Estevam (Universidade Federal Rural do Semi-Árido, 2019)
Parasite infections are worldwide spread, and the potential of these geo-helminthics diseases can range from mild symptoms, lowering productivity or slowing child development to severe cases of infection. The dissemination has diverse sources, most related to social condition, climate and sanitary habits. In hospital environments, due to the flow of people from different locations, associated with the divergent immunological situation of patients, the site becomes a source of contamination. The present work aimed to diagnose soil transmitted helminths of public health importance around health institutions. Therefore, five samples were collected at different points around each of the ten selected institutions, totaling 50 samples. These were submitted to sedimentation and flotation techniques to diagnose parasites in the soil. It was found that 100% (10/10) of the sites presented some type of parasite with pathogenic potential. Of the total samples 50% (25/50) were diagnosed with the presence of a parasitic agent of public health importance. The prevalence of parasites identified in the total samples was 76% (19/25) for Ancylostoma sp; 4% (1/25) for Ascaris sp and 24% (6/25) for Strongyloides sp. The results showed the presence of transmissible forms of parasites of importance in public health, demonstrating the need for attention of public agencies so that appropriate measures are applied to provide control and prevention of diseases that affect the well-being of the community
Monografia
Keywords: Parasitos; Areia; Geohelmintos; Contaminação; Saúde pública; Parasites; Sand; Geohelminths; Contamination; Public health; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA